EFEK INTRA INDUSTRI, DAMPAK PERUSAHAAN REPORTER DAN NONREPORTER DIVIDEN TERHADAP KANDUNGAN INFORMASI - Emrinaldi Nur DP; Enny Susilowati Mardjono (University of Merdeka Malang, 2013)
The influence of information not only for company itself which announcement company policy like financialstatement, dividend or others, but also the other company in same industry or same market. The purpose of theresearch was to investigate the information content and intra industry effect of dividend announcement. Theanalysis include four aspects: information content, risk (beta), intra industry effect of dividen by big and smallsize firms, and impact firm characteristics to abnormal return nonreporter firm.The analysis for informationcontent, risk (beta), intra industry effect used event study and for impact of firm characteristics used multiplelinier regressions.Result of this research showed that there was information content around the date of dividendannouncement, but there was no difference between abnormal return by big and small size firms. Thedifference between beta before and after dividend announcement is not significant. The difference between betabig size firms and small size firms after dividend announcement is not significant. The intra industry effect ofdividend announcement showed abnormal return with two effects: competitive effect and contagion effect. Thefirm specific characteristics used in this research were not significant to explain the fenomena intra industry.